(untitled) (Revista Ifes Ciência, 2021)
The objective of this study was to adjust and validate mathematical models to estimate physical and chemical characteristics of pineapple fruits (Ananas comosus L.) through their linear dimensions. For this purpose, 130 fruits of the cultivar BRS Vitória were used, produced at the experimental farm of the Capixaba Institute of Research, Technical Assistance and Rural Extension, located in the municipality of Sooretama, North of the State of Espírito Santo, Brazil. Of all fruits, the length (L), diameter (D), mass (M), titratable acidity (TA) and soluble solids (SS) were determined. For the modeling, the characteristics M, TA and SS were used as a dependent variable in function of L and D of the fruits, being adjusted the models of equation of first degree linear, quadratic and power. All equations were valid, thus obtaining the mean absolute error, root mean square error and Willmott d index. The diameter showed a better relationship with the physical and chemical characteristics of the pineapple fruit cultivar BRS Vitória, the equations being , e more suitable for estimating the mass, titratable acidity and soluble solids respectively, in a simple, safe and without the need to destroy the fruits.